1996
DOI: 10.1111/j.1432-1033.1996.0827p.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Escherichia coli of Sin a 1, the Major Allergen from Mustard

Abstract: Sin a 1, the major yellow mustard allergen, is a seed storage protein that belongs to the 2 s albumin family. It is composed of two disulfide-bonded polypeptide chains. The cloning of this allergen has been carried out by means of the polymerase chain reaction using non-degenerate oligonucleotides encoding the N-terminal and C-terminal regions of the mature protein as primers. Five genomic nucleotide sequences have been analyzed, encoding both mature polypeptide chains linked by the internal processed fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Over the past years, several cross-reactive allergens in fruits and other vegetable foods were identified that could play a role. Among these are thaumatins, chitinases and 2S-albumins [66, 67, 68, 69, 70, 71, 72, 73]. At the same time, we have to realize that clinical histories in this study were not confirmed by double-blind placebo-controlled food challenges.…”
Section: Discussionmentioning
confidence: 82%
“…Over the past years, several cross-reactive allergens in fruits and other vegetable foods were identified that could play a role. Among these are thaumatins, chitinases and 2S-albumins [66, 67, 68, 69, 70, 71, 72, 73]. At the same time, we have to realize that clinical histories in this study were not confirmed by double-blind placebo-controlled food challenges.…”
Section: Discussionmentioning
confidence: 82%
“…2S albumins possess two structural properties that make their recombinant production difficult: first, they are Cys-enriched proteins with a high concentration of disulfide bonds, and second, they present a complex molecular design with two different subunits joined by this type of Cys-Cys bridges. Previous attempts at expressing a properly folded rSin a 1 in E. coli always failed [19, 20]. The genetic organization of their genes makes feasible a biotechnology strategy using the precursor forms for the recombinant production of these heterodimeric proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The precursor form of Sin a 1 was cloned and produced as a recombinant protein in the bacteria Escherichia coli [19, 20]. However, this expression system failed in terms of yield and solubility probably due to the incorrect formation of disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only four major allergens from yellow mustard ( S. alba ) have been identified, namely: (a) Sin a 1, characterized as a seed storage protein napin and belonging to the 2S albumin family with a molecular weight (MW) of 14 kDa [12,13,14,15,16,17,18]; (b) Sin a 2, belonging to the seed storage 11S globulin with a MW of 51 kDa dissociated in two chains of 36 and 23 kDa [19,20]; (c) Sin a 3, a non-specific lipid transfer protein/nsLTP lipid transfer protein, 12 kDa [21]; and (d) Sin a 4, profilin, 13–14 kDa [21,22]. From the oriental mustard, Bra j 1, a seed storage protein from the 2S albumin family with a MW of approximately 16 kDa has been also identified as a major mustard allergen [23,24].…”
Section: Introductionmentioning
confidence: 99%